2017
DOI: 10.2355/isijinternational.isijint-2016-417
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ti Content on the Characteristics of Inclusions in Al–Ti–Ca Complex Deoxidized Steel

Abstract: Experiments with different titanium addition were carried out in alumina crucible without slag at 1 873 K to investigate the variation of inclusion composition, size and morphology in Al-Ti-Ca complex deoxidized steel. The samples exacted from the experimental steels were analyzed by field emission scanning electron microscopy (FE-SEM) and energy dispersive spectroscopy (EDS). Titanium influence significantly on the morphology, size distribution and composition of oxide inclusions in Al-Ca deoxidized steels, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…The presence of titanium in Al-killed molten steel generally causes more severe clogging of the submerged entry nozzle than Ti-free steel, and the titanium oxide inclusions have been suggested as a possible cause. [26][27][28] Thus, many studies of nonmetallic inclusions in Al-killed Ti-bearing steel have been carried out, such as nozzle clogging behavior, 26,28) thermodynamics and characteristics of inclusions, [29][30][31][32][33][34][35][36][37][38][39][40] modification of inclusions with Ca treatment [41][42][43][44][45][46][47] or Mg treatment [48][49][50][51][52] and evolution of inclusion during solidification and heating. 41,48,[53][54][55] The two-layered inclusions of the Al-Ti-O phase with core Al 2 O 3 were observed in Al-killed Ti-bearing molten steel, which was identical to the inclusions causing the nozzle clogging.…”
Section: Evolution Mechanism Of Inclusions In Al-killed Ti-bearing 1mentioning
confidence: 99%
“…The presence of titanium in Al-killed molten steel generally causes more severe clogging of the submerged entry nozzle than Ti-free steel, and the titanium oxide inclusions have been suggested as a possible cause. [26][27][28] Thus, many studies of nonmetallic inclusions in Al-killed Ti-bearing steel have been carried out, such as nozzle clogging behavior, 26,28) thermodynamics and characteristics of inclusions, [29][30][31][32][33][34][35][36][37][38][39][40] modification of inclusions with Ca treatment [41][42][43][44][45][46][47] or Mg treatment [48][49][50][51][52] and evolution of inclusion during solidification and heating. 41,48,[53][54][55] The two-layered inclusions of the Al-Ti-O phase with core Al 2 O 3 were observed in Al-killed Ti-bearing molten steel, which was identical to the inclusions causing the nozzle clogging.…”
Section: Evolution Mechanism Of Inclusions In Al-killed Ti-bearing 1mentioning
confidence: 99%
“…For Al-killed molten steel, calcium treatment is carried out as a routine technology in steelworks in order to solve the clogging of SEN during CC process, which can effectively modify the solid alumina and spinel (MgO•Al 2 O 3 ) inclusions to liquid calcium aluminate inclusions [40][41][42]. Many researchers [40][41][42][43][44][45][46][47][48] have investigated the evolution mechanism, reaction steps and reaction kinetics, morphology and size characteristics of aluminate-based inclusions in Al-killed molten steel during calcium treatment process on both thermodynamics and experiment scale. It was found that the evolution followed route of 'Al 2 O 3 →MgO•Al 2 O 3 →CaO-Al 2 O 3 -MgO' during the refining process [39,41,42].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of Ti addition on inclusions in Alkilled steels have been widely investigated, including the effect of the sequence of Ti addition, Ti/Al ratio, Ti content, and evolution behavior of inclusions. [17][18][19][20][21][22] Zheng et al [23,24] investigated Al-Ti complex deoxidization and concluded that the evolution of inclusions depended strongly on the Al content. Kim and Thapliyal et al [25,26] reported that Mn-Si-O inclusions decreased in number and even disappeared upon addition of Ti to molten steel.…”
Section: Introductionmentioning
confidence: 99%